The Evolution of Biologic Therapies for Psoriasis and Atopic Dermatitis: A Systematic Review of Randomized Controlled Trial - Claudia Felicia Limanda; Ericko Hartanto; Elisa Putri; Nurzanah Primadani; Multiyus Hasnah (Medicinus, 2026)
ground: Psoriasis and atopic dermatitis are chronic, immune-mediated inflammatory skin diseases that cause a substantial, lifelong burden on patients globally. Over the past two decades, the therapeutic paradigm has shifted dramatically from broad immunosuppression to highly targeted biologic therapies designed to interrupt key cytokine pathways driving clinical disease activity. Methods: To comprehensively evaluate this transition, we conducted a systematic review of randomized controlled trials assessing the efficacy and safety of biologic treatments for moderate-to-severe psoriasis and atopic dermatitis. We systematically searched major electronic databases for peer-reviewed published trials, extracting data on targeted mechanisms, clinical efficacy outcomes, and safety profiles. Result: The evolution in psoriasis treatment progressed sequentially from early tumor necrosis factor inhibitors to highly specific interleukin (IL)-12/23, IL-17, and selective IL-23 blockades. These newer agents consistently demonstrate unprecedented rates of complete skin clearance and durable responses. Similarly, the atopic dermatitis landscape has been revolutionized by biologics targeting type 2 inflammation, particularly the IL-4 and IL-13 pathways. These interventions provide profound relief from intractable pruritus and persistent lesions in patients refractory to conventional therapies, while largely avoiding the off-target toxicities of older systemic agents. Conclusions: The advent and evolution of biologic therapies represent a watershed moment in dermatology. By enabling precision immunology, these targeted treatments have fundamentally transformed disease management, offering patients realistic expectations for sustained remission and significantly enhanced quality of life.